Kemiskinan di Indonesia: Analisis penyebab, dampak, dan solusi kebijakan - Khariroh, Najwa Elok (Maliki Interdisciplinary Journal, 2025)
Poverty remains one of the biggest challenges faced by Indonesia, despite experiencing significant economic growth over the past few decades. Although the poverty rate has gradually decreased, millions of people still live below the poverty line, especially in remote areas. Regional disparities, low quality of human resources, and several interrelated factors continue to exacerbate poverty. This article aims to examine the underlying causes of poverty in Indonesia, its impacts on society, and policy solutions that can be implemented to address the issue. It is hoped that poverty in Indonesia can be significantly reduced in the long term and in a more equitable manner, reaching even the most remote areas.